Comparative Risk Prioritization in the Initiation Phase of the Pagerungan Besar Photovoltaic Plant: A Failure Mode and Effect Analysis (FMEA) and Risk Matrix Approach - Retnaningtias, Agustina Dwi; Ahyudanari, Ervina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Photovoltaic (PV) power plant projects in East Java often face challenges during the initiation phase due to inadequate risk assessments. This phase is crucial for ensuring the project's long-term success; however, suboptimal risk identification has caused project delays. In the risk assessment process, high-priority risks need to be mitigated, but differences in the methods used can result in varying risk priority outcomes. One of the methods that can be used is Failure Mode and Effect Analysis (FMEA), while according to internal regulations at PT PLN (Persero), the Risk Matrix is applied. By using these two methods, the differences in the resulting risk priority rankings can be identified. Both tools rely on evaluations from experts experienced in decision-making during the initiation phase of PV power plant projects. From the analysis, 12 risks were identified during the initiation phase of the Pagerungan Besar PV power plant project. The highest-priority risks identified include Suboptimal feasibility study (Risk Priority Number/RPN: 74.27), unfavorable outcomes for the organization/company (RPN: 68.96), lack of budget (RPN: 64.00), and stakeholder Intervention (RPN: 53.69). Meanwhile, by plotting the Severity Level and Occurrence Level of each risk on the Risk Matrix according to PT PLN (Persero) regulations, the highest-priority risks identified include Suboptimal feasibility study (Extreme Risk Level, Zone E5), location-related issues (Extreme Risk Level, Zone E5), non-compliance with regulations (Extreme Risk Level, Zone E5), and suboptimal project team (Very High Risk Level, Zone D5). The two risk assessment methods produced different prioritizations, potentially impacting mitigation strategy decisions. This variation highlights the need for further analysis to ensure accurate and reliable risk prioritization, which is critical for project success and efficient resource allocation. Future studies should focus on evaluating prioritization methods to support effective decision-making and ensure timely project implementation in line with the targeted Commercial Operation Date (COD).